THE EFFECT OF ENTREPRENEURSHIP ORIENTATION AND MARKET ORIENTATION ON MARKETING PERFORMANCE OF FURNITURE HOME INDUSTRY IN SAWAHAN DISTRICT - Sudarmadji, Chatarina Felisia; Sidharta, Helena; Wiryakusuma, I Gusti Bagus Yosia (Review of Management and Entrepreneurship, 2020)
This study analyzes the effect of entrepreneurial orientation and market orientation on the marketing performance of furniture home industry in Sawahan District. The objectives of this research are to: (1) determine the effect of entrepreneurial orientation on marketing performance (2) determine the effect of market orientation on marketing performance. The population in this study were 158 furniture home industry businesses in Sawahan District, Surabaya. The number of samples taken is 113 respondents which was determined using the Slovin formula. By using a quantitative research approach, the sampling technique used in this study used a random sampling method. Source of data obtained in this study is through the process of distributing questionnaires to 113 respondents in the home furniture industry in the District of Sawahan. The analytical tool used was SPSS 22. The results of the research obtained are that (1) entrepreneurial orientation do not significantly influence the marketing performance of furniture home industry in Sawahan District (2) Market orientation do not significantly influence the marketing performance of furniture home industry in Sawahan District. From the results of the research, business actors can begin to implement entrepreneurial orientation and market orientation through real practice. External encouragement is needed by businesses through extension activities and intensive training given by the government to mentally equip and provide knowledge so the furniture home industry business owners in Sawahan District can maintain the sustainability of their businesses.